Uptake of Biosimilar Infliximab in the UK, France, Japan, and Korea: Budget Savings or Market Expansion Across Countries? - Kim, Yujeong; Kwon, Hye-Young; Godman, Brian; Moorkens, Evelien; Simoens, Steven; Bae, SeungJin (Frontiers in Pharmacology, 2020)
Objective: To compare the market dynamics of biosimilar infliximab among four OECD countries (UK, France, Japan, and Korea) where supply-side and demand-side policies varied greatly. Methods: A quarterly dataset covering October 2012 to March 2018 was constructed from the MIDAS-IQVIA International database. The sales value (in USD) and volume (in standard units) of originator infliximab and biosimilar products and their relative price in each country were compared. Results: With the introduction of biosimilars, the sales value of infliximab increased approximately 2.5 times in Korea whereas it slightly increased (1.2 times for France and the UK) or decreased (0.9 for Japan) in other countries. While stable market size dynamics were observed in the other countries, an escalating market size, attributable to the increase in originator infliximab, was observed in Korea. In the UK and France, which have aggressive demand-side policies, the sales volume of originator infliximab appreciably decreased after the entry of biosimilar infliximab while that of biosimilars increased; however, in Korea, which has supply-side policies based on price-linking with few demand-side policies, the volume of originator infliximab actually increased by 70% alongside a very limited increase in biosimilar infliximab. The lowest price ratio between biosimilar and originator infliximab was found in Japan, at 68%. In France and Korea, the prices of biosimilar infliximab were 99% and 95%, respectively, of the originator infliximab price. In the UK, the price of biosimilar infliximab started at 87% of that of originator infliximab and then decreased to 80% as the market matured. Conclusion: The uptake of biosimilar infliximab varied greatly, and in contrast to the UK, France, and Japan, the introduction of biosimilar infliximab resulted in market expansion in Korea, which can be explained by a lack of demand-side policies in Korea.